Conductive properties of heavy-rare-earth A2Ir2O7 iridates synthesized by the CsCl-flux method. (May 2023) - Staško, Daniel; Vlášková, Kristina; Proschek, Petr; Klicpera, Milan
Abstract: The A2 Ir2 O7 pyrochlores with A = rare-earth element have been the subject of intense scientific interest for their complex magnetic and conductive properties. The previous studies focused mainly on the light A members of the series. We report on the electrical resistivity and magnetoresistance of the heavy-rare-earth iridates (A = Dy - Lu), including newly synthesized Tm2 Ir2 O7 member. The measurements were performed on pelletized powder samples synthesized using the CsCl-flux. The transition from the semimetal/semiconductor to the insulating state is followed within the series. Related anomaly in electrical resistivity continuously broadens coming from A = Dy to Lu. Electrical resistivity increases by several orders (up to 6) of magnitude with decreasing temperature down to 2 K. The nature of the transition to the insulating state was discussed in the frame of various models, leaning towards the Slater mechanism without Brillouin zone-folding. Investigated iridates become insulating due to an opening of a gap at the Fermi level induced by the antiferromagnetic ordering. A negative magnetoresistance was observed for all members of the series. The highest resistivity drop to 8% of the zero-field value was revealed for Dy2 Ir2 O7 . Ferromagnetic Ir domain walls between antiferromagnetic domains were discussed to influence the measured quantities for A2 Ir2 O7 iridates. Highlights: Transport properties of polycrystalline rare-earth A2Ir2O7 iridium pyrochlores. Temperature dependence of electrical resistivity and magnetoresistance measurements. Investigated compounds: Dy2Ir2O7, Ho2Ir2O7, Er2Ir2O7, Tm2Ir2O7, Yb2Ir2O7, Lu2Ir2O7. Metal-insulator transition described in regards to Slater and Mott mechanisms. Magnetoresistance dependent on rare-earth magnetic moment.